Sistem Pemesanan Tiket Kapal Ferry Dengan Customer Relationship Management Berbasis Bot Telegram - Linus Evrianus Ama Kean; Yohanes Suban Belutowe (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This research aims to design and develop a ferry ticket booking application integrated with Customer Relationship Management (CRM) based on a Telegram bot. The application is expected to facilitate customers in booking ferry tickets online and enable companies to manage customer relationships more effectively. The research method used is the waterfall method, which consists of the stages of analysis, design, implementation, testing, and maintenance. This application will be built using the Python programming language and the Telegram Bot API library for bot development. The main features of this application include ticket booking, customer data management, ferry data management, and two-way communication between customers and the company via the Telegram bot.